Highly nanocrystalline Mg doped ZnFe2O4 powders for rapid and simultaneous adsorption of lead, copper, and cadmium heavy metals ions in synthetic/sea waters - Al-Najar, B; Modwi, A; Shaikh, MN; Bououdina, M; Albuflasa, H; Hankins, NP (Elsevier, 2024)
This research aims to investigate the effect of Mg doping on individual and simultaneous adsorption of Pb+2, Cu+2, and Cd+2 heavy metals in aqueous solution and in seawater samples, by Zinc ferrite nanoparticles. The Mg-doped Zinc ferrite nanoparticles are synthesized successfully by the sol-gel route and varying Mg concentrations. TEM, XRD, FTIR, Raman, and XPS characterizations confirm the cubic spinel structure of Zinc ferrite with a semi-spherical shaped nanosized particles (10–15 nm) irrespective of Mg doping content. The BET surface area manifests a significant increase within Mg doping (39.3 m2/g) compared with the pure zinc ferrite (28.4 m2/g). Accordingly, Mg-doped Zinc ferrite powders demonstrate considerable adsorption capacities for Pb+2 (143.5 mg/g), Cu+2 (117 mg/g), and Cd+2 (77 mg/g) within 2 h under optimized experimental conditions. The prepared nanopowders exhibit high selectivity towards Pb+2 in simultaneous adsorption in aqueous solutions (85 mg/g) and real seawater samples. Nonetheless, the selectivity of Pb+2 ions drops dramatically to 25 mg/g within real seawater samples due to the strong ionic strength of high-salinity seawater. This study provides insights into the importance of doped spinel ferrite nanoparticles in highly efficient, rapid, and simultaneous adsorption of heavy metals. Besides, it reveals the challenge of performing the adsorption process in real seawater.